Specific macrophage immunity to Sendai virus: macrophage aggregation in vitro with Sendai virus by cytophilic antibodies. - Watanabe, M (1975)
When a 24-h tube culture of rabbit alveolar macrophages was infected with Sendai virus, the rate of infected cells was found to be limited. Even at a multiplicity of infection (MOI) of 500 plaque-forming units per cell, an average of 63% cells was found to synthesize viral antigens stainable by direct immunofluorescence. When the macrophages obtained from rabbits hyperimmunized by an intravenous injection of Sendai virus were infected under the same in vitro conditions, the rate of antigen synthesis averaged a low as 23%. At the time of infection of alveolar macrophages from immunized rabbits (immune macrophages), cell aggregation at an MOI 50 and cell fusion at an MOI 500 were found 24 h after infection, and these reactions were never encountered after the infection of nonimmune macrophages. When the immune macrophages were either pretreated by trypsin or incubated in medium at pH 4.0, the infection no longer caused the aggregation. The supernatant fluid obtained after incubation at pH 4.0 contained neutralizing antibody to Sendai virus. Conversely, when nonimmune macrophages were incubated in the presence of rabbit anti-Sendai virus serum or purified immunoglobulin G, the same aggregation reaction occurred after virus infection. Ultraviolet light-killed Sendai virus could be used as the counterpart of alive virus in the same aggregation reaction. These results suggest that the aggregation reaction of the immune macrophages could be attributed to the presence of specific cytophilic antibodies on their surface.